A rare case of nonresterilized reinforced ETT obstruction caused by a structural defect: A case report. Issue 48 (December 2017) - Kim, Sang Ho; Park, A Yeon; Cho, Ho Bum; Yoo, Jae Hwa; Park, Sun Young; Chung, Ji Won; Kim, Mun Gyu
Abstract: Rationale: Various factors can cause ventilatory failure after endotracheal tube (ETT) intubation, which is associated with increased patient morbidity and mortality. Patient concerns: A 76-year-old woman who was diagnosed with a hemopericardium and suspicion of a major-vessel injury due to dislocation of the clavicular fracture fixation screw. Diagnosis: Non-resterilized reinforced ETT obstruction caused by a structural defect. Intervention: Endotracheal tube was exchanged. Outcomes: The ventilator profile showed rapid improvement. Lessons: Anesthesiologists should consider that a non-resterilized reinforced ETT may be defective. An ETT defect can cause high PIP and ETT obstruction without kinking or foreign materials.